PEMBUATAN ANTISERUM SALMONELLA O POLIVALEN MENGGUNAKAN ANTIGEN DAN KELINCI LOKAL - Bambang Supriyanta; Ullya Rahmawati (Journal of Nursing and Health, 2024)
Introduction: Typhoid fever is a disease caused by infection with Salmonella enterica subspecies enterica serotype typhi (S. typhi). Laboratory diagnosis of typhoid fever by bacteriological examination in serological tests requires Salmonella O Polyvalent Antiserum reagent which has been imported, so it is attempted to make Salmonella O Polyvalent Antiserum independently using local antigens and rabbits. Objective: to create polyvalent Salmonella O antiserum using local antigens and rabbits. Methods: experimental research design posttest without control group. Cultures of S typhi, S paratyphi A, S paratyphi B, S paratyphi C, each processed, then mixed, so that it becomes Polyvalent Salmonella O Antigen. Polyvalent Salmonella O Antigen mixed with Freunds Complete Adjuvant, injected sub cutaneously (s.c) in rabbits, after one and two weeks the following week injected s.c Polyvalent Salmonella O Antigen plus Freunds Incomplete Adjuvant. After one week from the last injection, blood was taken through the ear artery (auricular artery) (collection I), one week after collection I, blood was taken (collection II), one week after collection II, the last blood was taken (Collection III), serum was made, the titer was measured using a suspension of Salmonella O Polyvalent Antigen with a turbidity of 0.5 Mc Farland standard. Result: Salmonella O Polyvalent was highest in rabbit blood collection in Collection II, indicating that the optimal production of antiserum at that time. Conclusion: The mean titer of Polyvalent Salmonella O Antiserum was highest in rabbit blood collection at Collection II.